Curcumin induces apoptosis in human leukemic cell lines through an IFIT2-dependent pathway. Issue 1 (2nd January 2017) - Zhang, Yonglu; Kong, Yunyuan; Liu, Shuyuan; Zeng, Lingbing; Wan, Lagen; Zhang, Zhanglin
ABSTRACT: Curcumin, the primary bioactive component isolated from turmeric, has been shown to possess variety of biologic functions including anti-cancer activity. However, molecular mechanisms in different cancer cells are various. In the present study, we demonstrated that curcumin induced G2/M cell cycle arrest and apoptosis by increasing the expression levels of cleaved caspase-3, cleaved PARP and decreasing the expression of BCL − 2 in U937 human leukemic cells but not in K562 cells. We found some interferon induced genes, especially interferon-induced protein with tetratricopeptide repeats 2 ( IFIT2), were significantly upregulated when treated with curcumin in U937 cells by gene expression chip array, and further confirmed that the expression of IFIT2 was obviously higher in U937 than that in K562 cells by Western blot assay. In addition, inhibiting the expression of IFIT2 by shRNA in U937 rescued curcumin-induced apoptosis and exogenous overexpression of IFIT2 by lentiviral transduction or treating with IFNγ in K562 cells enhanced anti-cancer activity of curcumin. These results indicated for the first time that curcumin induced leukemic cell apoptosis via an IFIT2-dependent signaling pathways. The present study identified a novel mechanism underlying the antitumor effects of curcumin, and may provide a theoretical basis for curcumin combined with interferon in the cancer therapeutics.